Inhibition of polychlorinated dibenzo-p-dioxins and dibenzofurans by phosphorus-containing compounds in model fly ash. (October 2020) - Wang, Pei-Yue; Xu, Shuai-Xi; Chen, Zhi-Liang; Chen, Tong; Lin, Xiao-Qing; Ma, Yun-Feng; Zhang, Meng-Mei; Li, Xiao-Dong
Abstract: Waste incineration is a preferred method in China to dispose the municipal solid waste, but controlling the production of highly toxic polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans effectively during incineration is both challenging and imperative. In this study, the suppression of PCDD/Fs by various phosphorus-containing compounds was explored, and the mechanisms responsible for the inhibition were studied in detail. The experiments took place in a lab-scale vertical tubular reactor at 350 °C under a simulated flue gas (12 vol% O2 in N2 flow), and both the off-gases and residues were collected for PCDD/Fs analysis. The scanning electron microscopy and energy-dispersive X-ray spectroscopy were used to characterize the reaction residues. The experimental results revealed that NH4 H2 PO4 and (NH4 )2 ·HPO4 showed the highest inhibitory effect (57.2% and 57.3%, respectively) on the PCDD/Fs formation, followed by CaHPO4 with inhibition efficiency of 39.1%. In contrast, KH2 PO4 and K2 HPO4 barely inhibited the generation of the PCDD/Fs. The inhibitory effect of NH4 H2 PO4 and (NH4 )2 ·HPO4 was similar to that of nitrogen-based inhibitors. At the same time, it was proven that the inhibitory activity of CaHPO4 might be due to the reaction of it with Cu 2+ forming stable compounds. Highlights: The activity of the N/P inhibitors on the PCDD/Fs is dominated by NH4 + . [PO4 ] 3- ion alone cannot act as an effective inhibitor. Stabilizing metal catalysts might be the main inhibition mechanism of CaHPO4 .